A Cross-Country Study of Preferences for Choice Autonomy - Jana Freundt; Holger Herz (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We establish the existence of intrinsic preferences for choice autonomy, defined as a preference for own choice in the absence of any instrumental value of choice, in large general population samples in nine countries using a novel preference elicitation tool. We find that such preferences are widespread, but also reveal stark differences across countries. Within countries, individuals who place a higher value on self-reliance and personal identity exhibit stronger intrinsic preferences for choice autonomy. In our small cross-country sample, we find suggestive evidence that differences are correlated with power distance, but not with measures of individualism, and that differences are predictive of managerial decentralization across countries.
Keywords: D01; D9; 330; autonomy; individualism; preferences; culture